2021
DOI: 10.1111/mms.12864
|View full text |Cite
|
Sign up to set email alerts
|

Observations of parturition in humpback whales (Megaptera novaeangliae) and occurrence of escorting and competitive behavior around birthing females

Abstract: Documented cases of cetacean births in the wild are rare. While there are currently no direct observations of a complete humpback whale birth, they are one of the few large whale species where observers have been present during a birthing event. We compiled eye‐witnessed accounts of all known humpback whale birthing events and found nine well‐documented cases globally (three published and six “new” unpublished). In two‐thirds of the accounts another “escort” whale was present and in close association with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…Calving is generally expected in calm, shallow coastal or bank waters [65][66][67][68][69] and not in exposed oceanic waters. However, the observed changes in movement (i.e., from fast to very slow movement followed by a period of continuous movement at reduced speed) are consistent with the behavior reported from earlier observations of calving events [65,66,70]. Newborn calves have been documented outside of the described main breeding grounds elsewhere [26,71] and historical whaling records from Norway include records of late-stage pregnancies in Norwegian waters during winter and spring [72], also indicating humpback whales from this region might give birth shortly after these observations were made, likely outside breeding grounds [73].…”
Section: Plos Onesupporting
confidence: 90%
“…Calving is generally expected in calm, shallow coastal or bank waters [65][66][67][68][69] and not in exposed oceanic waters. However, the observed changes in movement (i.e., from fast to very slow movement followed by a period of continuous movement at reduced speed) are consistent with the behavior reported from earlier observations of calving events [65,66,70]. Newborn calves have been documented outside of the described main breeding grounds elsewhere [26,71] and historical whaling records from Norway include records of late-stage pregnancies in Norwegian waters during winter and spring [72], also indicating humpback whales from this region might give birth shortly after these observations were made, likely outside breeding grounds [73].…”
Section: Plos Onesupporting
confidence: 90%
“…In general, the maternal behavior during the parturition described here is similar to the behavior observed in other successful cetacean births, which may include thrashing (Zani et al, 2008), arched back positions (e.g., Weilgart & Whitehead, 1986), lurching and tail spasms (e.g., Leatherwood & Beach, 1975), and rotating (Stacey & Baird, 1997). No maternal assistance for calf surfacing immediately after birth was observed, as opposed to what has been documented in some other baleen whale birthing events (e.g., Ferreira et al, 2011; Zani et al, 2008), but not in all (see Foley et al, 2011; Ransom et al, 2022). Although it is difficult to determine when labor truly began, the behavior identified by the crew as a parturition event was short (<2 min) possibly explaining why these birthing events are so rare to observe and document (Ransom et al, 2022).…”
Section: Figurementioning
confidence: 63%
“…We examined how the body size (BAI and TL) of lactating mothers' influences the body size of their respective calves'. In this study, humpback whale calves ranged in length from 7.5 to 10 m (mean= 8.5 m), while on the breeding grounds, humpback whale calves ranged between 4 and 8 m in length, with a presumed birth length between 3.96 and 4.57 m (Clapham et al, 1999;Ejrnaes and Sprogis, 2022;Ransome et al, 2022). We found that calves' TLs were positively related to their mothers' TLs, meaning longer calves were associated with longer mothers (Figure 5).…”
Section: Body Size Of Mother-calf Pairsmentioning
confidence: 80%